Viewership of Korean Movies among Nigerian Undergraduates - Ramson Oloche Acheme; Solomon Abiodun Oyeleye; Steven Anu’ Adesemoye; Kayode Joshua Okunnade; Ijikelly Oluseun Olorunjueda (Britain International for Academic Research (BIAR-Publisher), 2025)
This study examines viewership of Korean films among Nigerian undergraduates. It took a descriptive survey of undergraduate students across various universities in Southwest Nigeria. The sample frame was narrowed down to mass communication undergraduates in six universities cutting across Lagos (Lagos State University of Science & Technology; NOUN-Ikorodu campus), Ogun (Christopher university) and Ondo (Adekunle Ajasin University- Akungba Akoko; Wesley University) States, respectively. While serving as an exploratory study, it was aimed at measuring the level of viewership and interest in Korean movies and, identify their preference for Korean and Nollywood movies. The researchers used the survey method of convenience sampling technique where link to a 15-item online questionnaire was shared through WhatsApp platforms to the select universities. Findings from the study revealed that Nigerian undergraduates watch Korean drama a lot. The study also found that, though many Nigerian youths enjoy and prefer Korean movies to Nollywood movies, there is a reasonable number of the youths who still prefer Nollywood movies. Therefore, the study concluded that the rising interest in Korean movies among Nigerian youth may not be harmful to their life. However, there is concern of addiction and craze for Korean beauty products. The researchers, therefore, recommend that Nigerian youths be sensitised on social media and on television, regarding the danger of getting obsessed with Korean beauty products as they try to look like the casts in Korean movies.